Effectiveness of Acupressure at the Zusanli (ST-36) Acupoint as a Comfortable Treatment for Diabetes Mellitus: A Pilot Study in Indonesia - Fitrullah; Addison Rousdy (Medical Association of Pharmacopuncture Institute, 2017)
Diabetes mellitus is a dangerous disease worldwide. Indonesia has 10 million diabetic and 17.9 million prediabetic citizens. Unfortunately, less than half of these diabetic individuals are aware of their conditions and less than 1% of those receiving medical treatment achieve their healing targets. Because acupressure is believed to be an effective treatment without the use of drugs, in this study we investigated acupressure as a comfortable and effective way of treating patients with diabetes mellitus. This pilot study involved 30 participants who were split into two groups: 15 each in the experimental and the control groups. The experimental group underwent acupressure at the Zusanli (ST-36) acupoint for 30 minutes per visit for 11 weeks, whereas the control group continued their regular treatment; participants in both groups had their blood glucose randomly checked weekly. Data were analyzed using the Generalized Estimating Equation model; the result showed that the two groups were significantly different (p=0.331 > α=0.05; mean difference=99.14; Bonferroni sig. p=0.000 < α=0.05) and that acupressure at ST-36 was effective in reducing blood sugar. This research showed that acupressure was an effective method for reducing blood glucose and was helpful for reducing complications due to diabetes.